2019
DOI: 10.1155/2019/6394784
|View full text |Cite
|
Sign up to set email alerts
|

MiR-455-5p Suppresses the Progression of Prostate Cancer by Targeting CCR5

Abstract: Accumulated evidence indicates that miR-455-5p functions as tumor suppressor in the progression of various cancers. However, the mechanism through which miR-455-5p influences the tumorigenesis of human prostate cancer (PCa) remains undetermined. In this study, reanalysis of data obtained from the Memorial Sloan Kettering Cancer Center showed that miR-455-5p can be used as biomarker for PCa diagnosis and predictor of poor prognosis. Functional assays indicated that miR-455-5p overexpression could suppress cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Reduced tumor xenograft growth [82] Maraviroc Reduced metastasis and improved overall survival (in presence of chloroquine) [144] miR-455-5p Inducted apoptosis, suppressed cellular proliferation, and tumor xenograft growth [145] Cancer-associated fibroblast, CAF; C-C chemokine ligand 5, CCL5; C-C chemokine receptor type 5, CCR5; colorectal cancer, CRC; enhancer of zeste homolog 2, EZH2; mCCR5-Ig, fusion protein that neutralizes all three CCR5 ligands; mesenchymal stem cells, MSC; myeloid-derived suppressor cell, MDSC; platelet-derived growth factor receptor, PDGFR; programmed death ligand 1, PD-L1; peripheral blood mononuclear cell, PBMC; shRNA short hairpin RNA; small interfering RNA, siRNA; tumor-associated macrophage, TAM; regulatory T cell, Treg.…”
Section: Anibaminementioning
confidence: 99%
See 2 more Smart Citations
“…Reduced tumor xenograft growth [82] Maraviroc Reduced metastasis and improved overall survival (in presence of chloroquine) [144] miR-455-5p Inducted apoptosis, suppressed cellular proliferation, and tumor xenograft growth [145] Cancer-associated fibroblast, CAF; C-C chemokine ligand 5, CCL5; C-C chemokine receptor type 5, CCR5; colorectal cancer, CRC; enhancer of zeste homolog 2, EZH2; mCCR5-Ig, fusion protein that neutralizes all three CCR5 ligands; mesenchymal stem cells, MSC; myeloid-derived suppressor cell, MDSC; platelet-derived growth factor receptor, PDGFR; programmed death ligand 1, PD-L1; peripheral blood mononuclear cell, PBMC; shRNA short hairpin RNA; small interfering RNA, siRNA; tumor-associated macrophage, TAM; regulatory T cell, Treg.…”
Section: Anibaminementioning
confidence: 99%
“…CCR5 antagonist anibamine inhibited prostate cancer cell line growth with and without CCL5 stimulation in vitro, and decreased prostate cancer xenograft growth [81]. CCR5 is a target of miR-455-5p [145]. The down-regulation of CCR5 by miR-455-5p overexpression inhibited prostate cancer cell growth and induced apoptosis [145].…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In case of prostate cancer, the miR-455-5p tumor suppressor function has been shown to significantly suppress proliferation and initiate apoptosis of prostate cancer cells. The authors also experimentally determined a functional target for miR-455-5p -CCR5 gene [82].…”
Section: Downregulated Micrornas Associated With Lymphatic Disseminatmentioning
confidence: 99%
“…A high plasma level of CCL3 was associated with poor survival rate in chronic lymphocytic leukemia [ 66 ] and diffuse-large B-cell lymphoma [ 67 ]. CCR5 was reported to be associated with poor overall survival in breast cancer [ 34 ], poor relapse-free survival in prostate cancer [ 68 ], high histological grade in pancreatic cancer [ 35 ], and perineural invasion in salivary adenoid cystic carcinoma [ 36 ]. The present study is the first report which revealed that the expression of both CCL3 and CCR5 in human cancer tissue is associated with poor patient prognosis.…”
Section: Discussionmentioning
confidence: 99%